2009
DOI: 10.1007/s00394-009-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Fibre in beverages can enhance perceived satiety

Abstract: Our results support the idea that dietary fibre in beverages can enhance their perceived satiety and decrease the desire to eat more than a beverage without fibre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 20 publications
1
56
2
1
Order By: Relevance
“…DF is resistant to digestion and absorption in the human small intestine, with complete or partial fermentation taking place in the large intestine (AACC, 2001). High fibre foods increase the feeling of fullness, provide more nutrients with fewer calories and could help to reduce childhood obesity (Kimm, 1995;Lyly et al, 2009;Whelan, Efthymiou, Judd, Preedy, & Taylor, 2006). The use of less refined natural cell wall materials in foods has a number of benefits.…”
Section: Introductionmentioning
confidence: 98%
“…DF is resistant to digestion and absorption in the human small intestine, with complete or partial fermentation taking place in the large intestine (AACC, 2001). High fibre foods increase the feeling of fullness, provide more nutrients with fewer calories and could help to reduce childhood obesity (Kimm, 1995;Lyly et al, 2009;Whelan, Efthymiou, Judd, Preedy, & Taylor, 2006). The use of less refined natural cell wall materials in foods has a number of benefits.…”
Section: Introductionmentioning
confidence: 98%
“…β-Glucan from other sources has been shown to increase satiety. When 5 or 10 g of oat fibre (50% β-glucan) were added to a beverage, satiety was increased and hunger decreased compared with no-fibre control beverage (Lyly et al, 2009). The influence of viscous properties of oat β-glucan on gastric emptying and circulating levels of gut peptides (CCK, were clearly demonstrated by Juvonen et al (2009).…”
Section: β-Glucanmentioning
confidence: 88%
“…Increased fullness during 120 min (Lyly et al, 2009) (Levine et al, 1989) Extruded wheat bran cereal (57 g, 20.0 g df)…”
Section: Min N = 19mentioning
confidence: 99%
“…Howarth et al [30] suggested direct eVect of dietary Wbre on energy intake is the decreased absorption of macronutrients because of the physical barrier formed by dietary Wbre. One study has shown that the viscosity of soluble Wbres and oat -glucan had a role in their ability to increase satiety [45]. Fibre consumption has been shown to be associated with a reduced risk of overweight in children [28], but this assumption was not supported in the study by Ruottinen et al [58].…”
Section: Satietymentioning
confidence: 97%